Dental caries experience among qat chewers in dental college clinics, Jazan, Saudi Arabia - Esam Halboub; Abdulwahab Ahmed Alamri; Ghazi Kamili; Ahmed Shaher Alqahtani (BMC, 2023)
Abstract Aims There is a considerable debate on the impact of qat chewing on dental and oral health. Thereby, this study aimed at assessing the dental caries among qat chewers (QC) and non-qat chewers (NQC) who attend outpatient dental clinics, College of Dentistry, Jazan, Saudi Arabia. Materials and methods A sample of 100 QC and 100 NQC were recruited amongst those attended dental clinics, college of dentistry, Jazan University during the 2018-2019 academic year. Their dental health was assessed by three pre-calibrated male interns using DMFT index. The Care Index, Restorative Index and Treatment Index were calculated. Comparisons between both subgroups were done using independent t test. Multiple linear regression analyses were further conducted to stand on the independent determinants of the oral health among this population. Results QC were unintentionally older (36.55 ± 8.74 years) than NQC (32.96 ± 8.49 years; P = 0.004). Fifty-six percent of QC reported brushing their teeth compared to only 35% (P = 0.001). NQC with university and postgraduate educational levels were more than QC. The mean Decayed [5.91 (5.16)] and DMFT [9.15 (5.87)] were higher among QC compared to NQC [3.73 (3.62) and 6.7 (4.58); P = 0.001 and 0.001, respectively]. The other indices were not different between both subgroups. The multiple linear regression revealed that qat chewing and age, individually or together, as independent determinants for the dental decay, missing, DMFT and TI. Conclusion Qat chewing habit has a detrimental impact on dental health. It is associated with higher dental caries and missing teeth, and a lower treatment index.